Control interno de los ingresos y gastos de la Empresa Swtelecom S.A, en el cantón Babahoyo, los ríos, periodo 2022 - Rodríguez Cepeda, Cristhian Joan (2023)
The purpose of this work is to analyze the internal control of the income and expenses of the company Swtelecom S.A through the analysis of the financial information for the year 2022. Swtelecom, despite being a company that is in a market of constant innovation due to the Technological advances have presented several problems in the records of income and expense accounts, which are moderately affected by the lack of trained personnel and imprecise control over the reality of the accounts. In order to carry out this case study effectively, we have the necessary knowledge and sources of information and the main objective of this study is to analyze internal control of the company's income and expenses to determine the level of trust and the level of risk through of a question questionnaire based on the COSO Model.